Relationship between Sociodemographic Traits, Indoor PM2.5 Exposure, and Acute Respiratory Infection Risk in Aluminum Factory Communities, Deli Serdang - Faridah Hanum Rajagukguk; Nurmaini Nurmaini; Taufik Ashar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Acute Respiratory Infections (ARI) in the working area of Mulyorejo Public Health Center, where an aluminum factory is located, rank first among the ten most common diseases. This study aims to analyze the influence of sociodemographic characteristics and PM2.5 exposure on ARI complaints in the aluminum factory area of Payageli Village, Deli Serdang Regency. The cross-sectional observational study involved 160 housewives living within a radius of 10–1500 meters from the factory’s chimney. The analysis included univariate, bivariate, and multivariate methods. Results showed that 58.1% of respondents experienced ARI symptoms in the past month. The average ambient (outdoor) PM2.5 concentration measured from three sampling points was 12.3 µg/m³, which did not exceed the WHO standard (<15 µg/m³). The highest concentration was recorded in the southern direction (15.5 µg/m³). Bivariate analysis indicated that education (p = 0.010), direction of house location (p = 0.001), and indoor PM2.5 concentration (p = 0.006) were significantly associated with ARI. Multivariate logistic regression analysis showed that the most dominant factor influencing ARI was indoor PM2.5 concentration (p = 0.039), followed by education (p = 0.013) and direction of house location (p = 0.001). This study provides a scientific basis for air quality control and housing environment improvement to reduce the risk of environmentally related diseases in industrial zones.